SAVING CHOICES IN SOUTH ASIA: EVIDENCE FROM FORMAL, INFORMAL, AND DIGITAL CHANNELS (Contemporary Journal of Social Science Review, 2025)
This study analyzes individuals saving behavior in South Asia using a multi-channel approach. It distinguishes between formal bank saving, mobile money saving, informal saving, and saving through any channel. The analysis uses Global Findex Database 2024 microdata for Bangladesh, India, Nepal, Pakistan, and Sri Lanka (N = 6,984). Logit models are estimated to examine how demographic, socioeconomic, digital-access, and country factors shape saving choices. Education, income, and employment emerge as strong and consistent predictors, especially for formal bank saving. Digital access plays an important but uneven role. Mobile money saving is largely driven by country-level digital ecosystems, while informal saving is more common among women and rural households. Overall, saving channels coexist rather than replace one another, highlighting the need for inclusive and context-sensitive financial policies.